2011
DOI: 10.2174/1875043501104010054
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cells and Umbilical Cord as Sources for Schwann Cell Differentiation: their Potential in Peripheral Nerve Repair

Abstract: Schwann cells are important components of the peripheral glia that form myelin, serving as the microenvironment of nerve fibers in the peripheral nervous system (PNS). Damage to the PNS induces the differentiation and activation of Schwann cells to produce factors that strongly promote axonal regrowth, and subsequently contribute to remyelination, which is crucial for the recovery of function. Although the collection and transplantation of native Schwann cells are effective for the treatment of neural diseases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
22
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 108 publications
(147 reference statements)
2
22
0
Order By: Relevance
“…Recently, MSCs have been the focus of intensive investigations because of their relative advantages (22)(23)(24). The generation of MSC-NPCs from hUCB-MSCs can be used for basic research in order to develop effective cells for regenerative therapy (11).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, MSCs have been the focus of intensive investigations because of their relative advantages (22)(23)(24). The generation of MSC-NPCs from hUCB-MSCs can be used for basic research in order to develop effective cells for regenerative therapy (11).…”
Section: Discussionmentioning
confidence: 99%
“…The first report of induction system for differentiating Schwann cells from BM-MSCs appeared in 2001 (Dezawa et al 2001). Recent studies showed that UCMSCs differentiated into Schwann cells capable of supporting neural regeneration and in constructing myelin (Matsuse et al 2010;Kuroda et al 2011). Some studies suggest that UC-Schwan cells are viable alternatives to native Schwann cells and may be used for cell-based therapy for nerve injuries.…”
Section: Peripheral Nerve Repairmentioning
confidence: 99%
“…Schwan cells play important roles in axonal regeneration and myelin construction in spinal cord injuries. As Schwann cells can be differentiated from various sources of MSCs and not only from WJ, a vis-à-vis comparison of various sources of MSCs will reveal the potential of WJ-derived MSCs for therapeutic application in spinal cord injury (Kuroda et al 2011). Furthermore, human umbilical cord-derived MSCs (hUCMSCs) have been shown to ameliorate neonatal hypoxic-ischemic encephalopathy (HIE) in rat models (Zhang et al 2014).…”
Section: Peripheral Nerve Repairmentioning
confidence: 99%
“…In a further paper, Dezawa and co-workers [14] analyze the literature reports on the ability of WJC to differentiate towards Schwann cells. Given the intrinsic ability of activated Schwann cells to promote axonal regeneration in vivo, umbilical cord-derived MSC can be used to successfully derive mature Schwann cells for the regeneration of peripheral nerve.…”
mentioning
confidence: 99%